Proposta de estratégia para agilização do controle restaurativo de sistemas elétricos de potência - Guilherme Manganelli Lopes (2008)
This work proposes a strategy to improve Electrical Power System Restoration process after a blackout. The proposal is based on the integration of the functionalities and information that are available in operation centers. The strategy is applied on the proceedings steps in which the understanding of the contingency and the choice of the correct decisions are extremely important to the success of the recovery process, namely: the facilities preparation and the treatment of equipment impediments. This work presents also an application of the proposed strategy in the restoration process of an energy power utility, as a form of a detailed functional specification.